Answer:
The answer is <u>9</u>
Step-by-step explanation:
picture attached
1st:
f(x) = x^2.
f(x +1): Anywhere we see x we replace it with (x+1)
f(x+1) = (x+1)^2 , Expand
(x+1)^2 = (x+1)(x+1) = x^2 + 2x + 1= C.
2nd:
Noting general equation, y = mx + c
m = slope, c = vertical intercept.
From the graph, slope = (2,0) and (0, -4)
= (-4 -0) / (0 - 2) = -4/-2 = 2.
Vertical intercept, c = -4.
y = mx + c , y = 2x + (-4), y = 2x - 4 = D.
3rd:
f(x) = x^2 - x, f(-4). we would substitute x = -4.
f(-4) = (-4)^2 - (-4) = 16 + 4 = 20 = D.
Cheers.
Initial value of the function is 24
<span>f(x)=-x^2+10x+6
f(x)=3x^2-12x+9
f(x)=-2x^2+2x+7
f(x)=8-x^2 </span>
Answer:
216
Step-by-step explanation:
When you say "6 raised to 3", it means you multiply 6, 3 times. Meaning:
6✖️6✖️6=216
Hope this helped!
Have a nice day:)